(untitled) (Journal of Bio-Science, 2009)
Macrobrachium dayanum (Hall) is the second largest freshwater prawn found abundantly in Bangladesh, India and Pakistan in rivers. It is a boneless, tasty and lucrative food item. Very few works are available on the fecundity, metamorphosis and hatching of M. dayanum (Jalihall and Sankoli 1975, Katre and Pandian 1972). This lead to the present study. doi: 10.3329/jbs.v15i0.2160 J. bio-sci. 15: 173-174, 2007